ANALISIS PREFERENSI BAHASA INDONESIA PADA MAHASISWA UPN “VETERAN” JAWA TIMUR SEBAGAI PENGGUNA SISTEM INFORMASI BERBASIS WEBSITE - Aldi Bagus Hermawan; Muhammad Yustitio Hadi Utomo; Pramudya Abimanyu; Visnhu Arya Bhisma; Nala Widyadhana; Rido Izril Qotana; Sujatmiko Dwi Kuncoro; Endang Sholihatin (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2023)
This study aims to determine the preferences of Indonesian among UPN "Veteran" East Java students as users of a website-based information system, to determine the factors that influence the preferences of Indonesian students at UPN "Veteran" East Java as users of a website-based information system, and to find out the differences in Indonesian language preference for East Java "Veteran" UPN students as users of a website-based information system. This study used a quantitative research method by distributing questionnaires for data collection. The results of this study show that the preference for Indonesian among UPN "Veteran" East Java students is still high, at around 95% in the use of a website-based information system. Factors that influence preference for Indonesian among UPN "Veteran" East Java students as users of a website-based information system are 1) the ease of understanding information, 2) the convenience factor, and 3) the quality of Indonesian translation. In addition, differences in Indonesian language preferences among UPN "Veteran" East Java students as users of website-based information systems are due to several factors, namely the level of comfort and familiarity with using Indonesian in using website-based information systems, the frequency of using Indonesian in everyday life, and the level of confidence in the quality of access and ease of use of website-based information systems in Indonesian.